Coelacanths as “almost living fossils” - Cavin, Lionel; Guinot, Guillaume (Frontiers in Ecology and Evolution, 2014)
Since its usage by Darwin in 1859, the concept of ‘living fossil’ has undergone multiple definitions and has been much discussed and criticized. Soon after its discovery in 1938, the coelacanth Latimeria was regarded as the iconic example of a ‘living fossil’. Several morphological studies have shown that the coelacanth lineage (Actinistia) has not displayed critical morphological transformation during its evolutionary history and molecular studies have revealed a low substitution rate for Latimeria, indicating a slow genetic evolution. This statement, however, has been recently questioned by arguing that the low substitution rate was not real, and that the slow morphological evolution of actinistians was not supported by paleontological evidence. The assessment of morphological transformation among three vertebrate lineages during a time interval of circa 400 million years shows that the morphological disparity of coelacanths is much more reduced than the morphological disparity of Actinopterygii and Tetrapoda. These results support the idea that living coelacanths are singular organisms among the living world.